The impact of general sales agents on the air cargo industry - Hosie, Peter; Lim, M.; Chng, M. (Inderscience Publishers, 2012)
General Sales Agent (GSA) is an airline’s outsourcing counterpart that markets and manages cargo services. An empirical investigation is undertaken to ascertain whether GSAs contribute economically to the air cargo industry using three ‘litmus test’ indicators: contribution to the airline’s sales and profitability by expanding operating networks; viability as a marketing option for emerging or struggling airlines to help cut operating costs to reduce prices; cost-effective GSAs were found to establish an airline’s market presence through wide network coverage and good local knowledge, leading to an expansion of airline’s operating networks and generating greater sales revenue.